Good Corporate Governance dan Operasional Perusahaan terhadap Kinerja Perusahaan - Aulia Claraning Sukmawati; Oriza Herlina Amalia; Yuli Indri Sari (Entrepreneurship Faculty, Universitas Garut, 2021)
Abstract- This study aims to determine whether the components of good corporate governance, company operations and type of company ownership affect the firm's in companies listed on the Indonesia Stock Exchange. The population in this study are all companies listed as non-financial companies on the Indonesia Stock Exchange for the 2010-2019 period. The research sample was obtained by purposive sampling method, where there were 87 non-financial companies that met the sample criteria. This research was conducted using regression analysis, namely ordinary least squares (OLS), which aims to determine the influence of the independent variable on the dependent variable. The results showed that the frequency of board meetings 1 had a significant negative effect as indicated by the result that the number of